Characterization and mechanism of aflatoxin degradation by a novel strain of Trichoderma reesei CGMCC3.5218 - Yue, Xiaofeng; Ren, Xianfeng; Fu, Jiayun; Wei, Na; Altomare, Claudio; Haidukowski, Miriam; Logrieco, Antonio F.; Zhang, Qi; Li, Peiwu (Frontiers in Microbiology, 2022)
Aflatoxins, which are produced mainly by Aspergillus flavus and A. parasiticus, are recognized as the most toxic mycotoxins, which are strongly carcinogenic and pose a serious threat to human and animal health. Therefore, strategies to degrade or eliminate aflatoxins in agro-products are urgently needed. We investigated 65 Trichoderma isolates belonging to 23 species for their aflatoxin B1 (AFB1)-degrading capabilities. Trichoderma reesei CGMCC3.5218 had the best performance, and degraded 100% of 50 ng/kg AFB1 within 3 days and 87.6% of 10 μg/kg AFB1 within 5 days in a liquid-medium system. CGMCC3.5218 degraded more than 85.0% of total aflatoxins (aflatoxin B1, B2, G1, and G2) at 108.2–2323.5 ng/kg in artificially and naturally contaminated peanut, maize, and feed within 7 days. Box–Behnken design and response surface methodology showed that the optimal degradation conditions for CGMCC3.5218 were pH 6.7 and 31.3°C for 5.1 days in liquid medium. Possible functional detoxification components were analyzed, indicating that the culture supernatant of CGMCC3.5218 could efficiently degrade AFB1 (500 ng/kg) with a ratio of 91.8%, compared with 19.5% and 8.9% by intracellular components and mycelial adsorption, respectively. The aflatoxin-degrading activity of the fermentation supernatant was sensitive to proteinase K and proteinase K plus sodium dodecyl sulfonate, but was stable at high temperatures, suggesting that thermostable enzymes or proteins in the fermentation supernatant played a major role in AFB1 degradation. Furthermore, toxicological experiments by a micronucleus assay in mouse bone marrow erythrocytes and by intraperitoneal injection and skin irritation tests in mice proved that the degradation products by CGMCC3.5218 were nontoxic. To the best of our knowledge, this is the first comprehensive study on Trichoderma aflatoxin detoxification, and the candidate strain T. reesei CGMCC3.5218 has high efficient and environment-friendly characteristics, and qualifies as a potential biological detoxifier for application in aflatoxin removal from contaminated feeds.